Physiological Alterations in Deletion Mutants of Two Insulin-Like Peptides Encoded in Maruca vitrata Using CRISPR/Cas9 - Al Baki, Md. Abdullah; Kyo Jung, Jin; Kim, Yonggyun (Frontiers in Physiology, 2021)
Most insect species encode multiple insulin-like peptides (ILPs) that exhibit functional overlaps in mediating physiological processes such as development and reproduction. Why do they need multiple ILPs? To address this question, we tested a hypothesis of the requirement of multiple ILPs by generating mutants lacking individual ILP genes using the CRISPR/Cas9 technology. Two ILPs (ILP1 and ILP2) in the legume pod borer, Maruca vitrata, are known to mediate similar physiological processes such as hemolymph sugar level, larval development, and adult reproduction. Individual knock-out mutants (∆ILP1 and ∆ILP2) were generated. They showed successful development from larvae to adults. However, they suffered from high hemolymph sugar levels by enhancing trehalose titers in the hemolymph. The hyperglycemic effect was more evident in ∆ILP2 mutants than in ∆ILP1 mutants. Both mutants showed increased expression of trehalose-6-phosphate synthase, but suppressed expression of trehalase. These mutants also showed altered expression patterns of insulin signaling components. Expression levels of insulin receptor and Akt genes were up-regulated while those of FOXO and Target of rapamycin genes were down-regulated in these mutants. These alterations of signal components resulted in significant retardation of immature development and reduced body sizes. ∆ILP1 or ∆ILP2 females exhibited poor oocyte development. Bromo-uridine incorporation was much reduced at the germarium of ovarioles of these mutants compared to wild females. Expression of vitellogenin gene was also reduced in these mutants. Furthermore, males of these deletion mutants showed impaired reproductive activities when they mated with wild type females. These results suggest that both ILPs are required for mediating larval development and adult reproduction in M. vitrata.